GAMBARAN ASPEK PERKEMBANGAN ANAK USIA TODDLER - Sumiati Sinaga (ITKES Wiyata Husada Samarinda, 2019)
Background : The golden age for children is in the age range of the first 1-3 years. At this time, the success of stimulation has a major influence on the child's development before the child enters the next phase of the stage of his age, namely pre-school children. Objective : to find out the description of the development of toddler age children in the work area of Baqa Samarinda Health Center. Method : This study uses descriptive research method with accidental sampling technique. The study sample was 78 children. Data collection is obtained through DDST II test. The results of the study : the development of normal personal social children as many as 59 children (75.6%), advanced as many as 5 children (6.4%), caution as many as 11 children (14.1%), delay as many as 3 children (3.8%). Normal fine motor aspects were 63 children (80.8%), advanced as many as 10 children (12.8%), caution as many as 3 children (3.8%), delay as many as 2 children (2.6%). Normal language aspects were 59 children (75.6%), advanced as many as 6 children (7.7%), caution as many as 9 children (11.5%), delay as many as 4 children (5.1%). Normal gross motor aspects were 56 children (71.8%), advanced as many as 19 children (24.4%), caution as many as 2 children (2.6%), delay as many as 1 child (1.3%). Conclusion : most of the development of normal children were 64 children (82.1%) suspected of 13 children (16.7%) and could not be tested by 1 child. Suggestion : We recommend that parents, especially mothers, can pay attention to their child's development by stimulating the 4 aspects of development so that their development can reach optimal level.